QUESTION LEVELS AND QUESTIONING SKILLS IN ELT (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Asking questions in English language teaching has a very important role to play. Questioning skills are the components of CTL, basic skill of teaching and one of the components of scientific approach that a teacher uses in teaching learning process. It is also believed that the quantity and quality of questions used by teachers will determine the quantity and quality responses given by students in ELT. In addition, English teachers should take into consideration question levels to ask to their students. One important consideration in asking questions is English proficiency level of students. Therefore, English teachers should be able to use various levels of questions beginning from lower to higher question levels. Bloom categorizes questions into six levels namely knowledge, comprehension, application, analysis, synthesis, and evaluation levels. While Anderson, Bloomâs former student, categorizes questions into remembering, understanding, applying, analyzing, evaluating, and creating. Questions used by teachers can be in the forms of yes/no questions, information questions and alternative questions. These forms of questions can be classified into display and referential questions. Other terms used to classify questions are convergent and divergent questions. By having enough knowledge, teachers are expected to be able to use various question levels and questioning skill in the classroom so that the participation of students can be improved and teaching learning process can run smoothly and successfully.Key words: question, questioning, display question, referential question, convergent and divergent questions.